Strategi Manajemen Keberlanjutan dalam Era Digital: Tantangan dan Peluang - Roberto Surya Negara (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to explore sustainability management strategies in the context of the digital era, focusing on the challenges and opportunities arising from technological transformation. In an era where digital technology increasingly dominates various aspects of life, organizations are faced with the need to adapt and integrate sustainability principles into their business practices. The research methods used were qualitative and quantitative analysis, including a literature review, interviews with experts in the fields of sustainability and technology, and a survey of companies implementing sustainability strategies. The results show that despite challenges such as resistance to change and the need for high initial investment, the opportunities offered by digital technologies, such as big data analytics and automation, can increase efficiency and transparency in sustainability practices. The implications of this study emphasize the importance of collaboration between the public and private sectors, as well as the need for education and training to increase awareness and understanding of sustainability among stakeholders. This research is expected to provide deeper insights into how organizations can leverage digital technology to effectively achieve their sustainability goals.